2020
DOI: 10.1186/s40345-020-00197-y
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of mindfulness-based cognitive therapy for people with bipolar disorder: a qualitative study

Abstract: Background Mindfulness- Based Cognitive Therapy (MBCT) could be a promising psychosocial intervention for people with bipolar disorder (BD). However, little is known about the feasibility of MBCT for people with BD. In this study we explore the facilitators and barriers people with BD experience of an adapted MBCT program. Method This qualitative study is part of a large, multicenter randomized controlled trial on MBCT for BD (trial registration number: NCT03507647). The present study included 16 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…This would resonate with findings in a recent network meta-analysis showing that adjunctive psychotherapy is the best option in stabilising episodes and preventing recurrences in BD, while at the same time heterogeneity in study populations was found to temper this finding (Miklowitz et al, 2021 ). Furthermore, as participants in our qualitative study indicated that they experienced the lack of follow-up sessions as a barrier to maintain their meditation practice (Hanssen et al, 2021b ), future research should investigate whether including booster sessions after MBCT increases long-term adherence and effectiveness. Moreover, the use of ecological momentarily assessments by interviews and self-report questionnaires in a highly recurrent and alternating disorders such as BD might be questionable.…”
Section: Discussionmentioning
confidence: 99%
“…This would resonate with findings in a recent network meta-analysis showing that adjunctive psychotherapy is the best option in stabilising episodes and preventing recurrences in BD, while at the same time heterogeneity in study populations was found to temper this finding (Miklowitz et al, 2021 ). Furthermore, as participants in our qualitative study indicated that they experienced the lack of follow-up sessions as a barrier to maintain their meditation practice (Hanssen et al, 2021b ), future research should investigate whether including booster sessions after MBCT increases long-term adherence and effectiveness. Moreover, the use of ecological momentarily assessments by interviews and self-report questionnaires in a highly recurrent and alternating disorders such as BD might be questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Random selection of participants for evaluation was not performed in any study. Two studies had a follow‐up rate of ≥80% (Ives‐Deliperi et al, 2013; Van Dijk et al, 2013), while six studies show an attrition rate of over ≥20% (Eisner et al, 2017; Hanssen et al, 2020; Painter et al, 2019; Pankowski et al, 2017; Perich et al, 2013; Weber et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Some differences were noted in the studies included in these reviews compared those in meta‐analysis. For example, in the Lovas and Schuman‐Olivier (2018) study, MII interventions are not included, while in Bojic and Becerra (2017) and Miziou et al (2015), due to the year of implementation, five articles are not included (Biseul et al, 2017; Eisner et al, 2017; Hanssen et al, 2020; Painter et al, 2019; Pankowski et al, 2017). Regarding the meta‐analyses published to date (Chu et al, 2018; Xuan et al, 2020), these do not include MII interventions, so for the ES calculations, our work includes 13 studies with respect to the seven by Chu et al (2018) and nine by Xuan et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…There were also practical barriers to participation: having other responsibilities, limited social support, too much pain, and too many mental complaints. Having limited time and practical/social support have also been identified as barriers in other studies on feasibility of MBIs in patients using opioids for chronic pain (Zgierska, Burzinski, Cox, Kloke, Singles, et al., 2016 ) as well as in different populations with somatic or psychiatric complaints (Brintz et al., 2020 ; Ewais et al., 2020 ; Hanssen et al., 2020 ; Janssen et al., 2020 ; Schoultz et al., 2016 ). To overcome these practical issues, MBCT could be offered in an individual, online format, where patients can follow the eight sessions in their own pace from home.…”
Section: Discussionmentioning
confidence: 99%